Side effects of progress: How technological change increases the duration of unemployment - William J. Baumol; Edward N. Wolff (Levy Economics Institute of Bard College, 1998)
Why does a dynamic growing economy have a persistent long-term unemployment problem? Research Associates Baumol and Wolff have isolated one cause. Although technological change, the engine of growth and economic progress, may not affect or may even increase the total number of jobs available, the fact that it creates a demand for new skills and makes other skills obsolete can cause an increase in the overall rate of unemployment and the length of time during which an unemployed worker is between jobs. It goes without saying that society will not choose to slow technical innovation, but the task for policy is to find ways to offset the problems caused by this rising level and duration of unemployment.
Keywords: 330